Determination of Sensor Network Coverage using Probabilistic Approach - Gorecki, J.; Miedzinski, B.; Nouri, H. (Elektronika ir Elektrotechnika, 2011)
Paper elaborates the method to identify near and far coverage area for each sensor estimating quality of service parameters in order to assess the areas of sensor redundancy and shortage. Coverage in near area is used to identify whether single sensor is enough to cover this area (sensor shortage indicating denser sensor layout). Coverage in far area is used to identify which sensors can be removed from the field in order to have lower cost of deployment of sensor network (sensor redundancy). Ill. 3, bibl. 7, tabl. 1 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.111.5.345